Post-Truth's Effect on the Brain and the Future Self: A Critical Communication Pedagogy Response - David H. Kahl Jr (Central States Communication Association, 2024)
The university was created for the critical examination of ideas to seek truth. However, the proliferation of post-truth messages has made this goal more difficult to reach, creating an important communication pedagogy problem. Hegemonic forces create post-truth messages to mislead people and play to their existing beliefs in order to maintain and advance power. Post-truth messages are particularly effective because they cause cognitive overload and temporal discounting. Critical communication pedagogy (CCP) is a means by which instructors and students can evaluate post-truth messages. CCP allows for dialogue to reduce the cognitive issues that post-truth messages cause and allow for the critical evaluation of post-truth messages for their (lack of) veracity. Doing so can lead students to take action to resist post-truth messages and their effects.